Proceedings of the Symposium on Detector Research and Development for the Surperconducting Super Collider, October 15-18, 1990, Fort Worth, Texas (World Scientific, 1991)
"Over the last three years a significant program of detector technology research and development for high luminosity, high energy hadron-hadron colliders has been underway in the United States, Japan and Europe. In as much as the first formal steps have been undertaken to initiate the experimental program at the Superconducting Super Collider (SSC), it is appropriate to assess in detail the status of this R&D effort"--